Effects of thermal radiation on mixed convection flow over a permeable vertical shrinking flat plate in an Oldroyd-B fluid - Kohilavani Naganthran; Roslinda Mohd. Nazar; Pop, Ioan (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study offers the numerical solutions for the problem of mixed convection stagnation-point flow along a permeable vertical flat plate in an Oldroyd-B fluid. The present investigation considers the effects of thermal radiation and heat generation/absorption in the fluid flow. The similarity transformation simplifies the complex model and the bvp4c function generates the numerical solutions according to the variations in the governing parameters. A higher degree of shrinking hastens flow separations. The dual solutions are visible in the range of buoyancy opposing flow. The results from this study may be useful for the scientist to understand the behaviour of the dilute polymer solutions in the industrial applications, for example, the drag reduction in pipe flows.